Denial and Repression of Antisemitism - Jovan Byford (Central European University Press, 2008)
Bishop Nikolaj Velimirović (1881-1956) is arguably one the most controversial figures in contemporary Serbian national culture. Having been vilified by the former Yugoslav Communist authorities as a fascist and an antisemite, this Orthodox Christian thinker has over the past two decades come to be regarded in Serbian society as the most important religious person since medieval times and an embodiment of the authentic Serbian national spirit. Velimirović was formally canonised by the Serbian ...